2012
DOI: 10.1007/s11657-012-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of osteoporosis health knowledge and medication use in older adults with minimal trauma fracture

Abstract: Osteoporosis knowledge assessed by the OKAT did not improve in the 3 months after MTF in this cohort of literate older adults, although there was some evidence of improvements in health beliefs. Current care in osteoporosis does not increase patient knowledge about their disease adequately which may impair patient effectiveness in obtaining appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Six studies assessed HL and its impact on those with musculoskeletal diseases: chronic pain, 46 rheumatoid arthritis, 47,48 osteoporosis, 49 chronic low back pain, 50 and osteoarthritis. 51…”
Section: Musculoskeletal Diseasesmentioning
confidence: 99%
“…Six studies assessed HL and its impact on those with musculoskeletal diseases: chronic pain, 46 rheumatoid arthritis, 47,48 osteoporosis, 49 chronic low back pain, 50 and osteoarthritis. 51…”
Section: Musculoskeletal Diseasesmentioning
confidence: 99%
“…A previous hospital based study of patients to whom a GP visit was suggested following a minimal trauma fracture found only 25% of patients undertook the visit. (15) Analysis of the types of goals selected by participants on their Bone Plans indicated that the most difficult goal to achieve was the introduction of weight bearing exercise into their regular routine. This is similar to other researchers who have also found osteoporosis knowledge easier to change than behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Studies conducted in different countries (12,13) have shown that patients diagnosed with osteoporosis displayed limited knowledge about the disease and they did not consider it to be very serious even though there is significant evidence that following a first fracture the risk of subsequent fracture increases two to three fold. (14) An Australian study, (15) which assessed older patients' knowledge of osteoporosis after hospital admission for fracture, found that osteoporosis beliefs, knowledge and medication use remained poor in spite of the large amount of osteoporosis information available to patients in the public domain. Otmar et al (12) as part of the Geelong Osteoporosis Study (GOS), have suggested that public health messages to motivate behavioural change targeted at the large numbers of people at risk of osteoporosis outside of community health and hospital settings may be more effective than attempting to provide medical therapy.…”
Section: (Ii) Main Text Introductionmentioning
confidence: 99%
“…Some studies have revealed that education programmes for the elderly are effective in improving health promotion knowledge and behaviours 9 . Previous studies have shown positive results in patient education to improve the use of nonpharmacologic preventive measures for osteoporosis 10,11 . Knowledge of modifiable risk factors (smoking, lack of physical exercise, dietary habits) should be targed by prevention programmes.…”
Section: Discussionmentioning
confidence: 99%